Re-laparotomy in OBG: a clinical study - Bijjaragi, Bhagyashree; M. N., Amulya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: If laparotomy done within 60 days of primary surgery for the original disease it is called re-laparotomy. Aim of this study was to determine the risk factors causing re-laparotomy, the indications, management and outcomes of re-laparotomy. Methods: The study was conducted in the department of Obstetrics and Gynaecology, Vijayanagar Institute of Medical Sciences Hospital, Bellary, Karnataka. It is a 2 year prospective observational study of all the patients with re-laparotomy following operation done for obstetric or gynaecological indications. Results: Total 4105 patients underwent major surgery in two years between October 2013 to September 2015. Re-laparotomy was done in 10 cases. The incidence of re-laparotomy was 0.25% which is mainly for subacute intestinal obstruction, intraperitoneal haemorrhage, burst abdomen, PPH, rectus sheath hematoma. Conclusions: Hemorrhage, burst abdomen, infections are the main reasons for re-laparotomy after obstetric and gynaecological surgeries. Though the incidence of re-laparotomy is low and the outcome is favourable, several measures must be undertaken to prevent re-laparotomy such as careful surgical technique, meticulous hemostasis and strict asepsis should be maintained.